2017
DOI: 10.11648/j.sjph.20170504.12
|View full text |Cite
|
Sign up to set email alerts
|

Couples’ Opinion and Women’s Utilization of Postnatal Care Service in Wolaita Zone, Southern Ethiopia: A Community Based Mixed Study

Abstract: Postnatal period is the most neglected period though it is a critical phase in the lives of mothers and newborn babies. About 50 to 71 percent of maternal deaths occur during this period, particularly in the first few hours. Therefore, this study aimed to assess couples' opinion & women's utilization of postnatal care service in Wolaita zone, Southern Ethiopia, January 2016. A community based cross sectional study was employed using both quantitative and qualitative methods of data collection. Study subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 2 publications
9
2
0
Order By: Relevance
“…This implies that educated partners tends to promote health decision making autonomy of women. This finding is consistent with the studies by Kamiya [32] and Facha et al [33] who reported positive association between husbands' education and women's health autonomy. Nevertheless, it is important to note that this association was limited to primary and secondary education of partners but not partners who doi: 10.7243/2054-9865-4-5 had higher than secondary education.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This implies that educated partners tends to promote health decision making autonomy of women. This finding is consistent with the studies by Kamiya [32] and Facha et al [33] who reported positive association between husbands' education and women's health autonomy. Nevertheless, it is important to note that this association was limited to primary and secondary education of partners but not partners who doi: 10.7243/2054-9865-4-5 had higher than secondary education.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, highly educated husbands were more likely to involve their wives in household decision making. This observation has been supported by other studies which have also reported a significant positive association between husband's educational status and women's autonomy in seeking health care services for themselves [25,33].…”
Section: Determinants Of Women's Decision-making Autonomysupporting
confidence: 81%
See 1 more Smart Citation
“…Young mothers more likely utilize postnatal care service than older one. This finding is supported by local studies conducted in Wolayitta Zone, SNNPR [11], and in addition it is similar with a study conducted in Pakistan [16], from a review on African country [17]. This can be justified younger mothers are more likely to have greater exposure and more access to education.…”
Section: Discussionsupporting
confidence: 87%
“…The findings of this study showed that among 544 postpartum women, 318 (58.5%) obtained PNC during the first 6 weeks following delivery. This result is high compared with studies done in different areas (Arsi zone, Oromiya (23.4%) [9], Debra markos Town, Amhara (33.5%) [8], Halaba Kulito, SNNPR (47.9%) [10], Wolayitta, SNNPR (34.31%) [11], North Eastern Nigeria (16.9%) [12] and Nepal (43.2%) [13]. This may be attributed to the time difference that there could be improvement in accessing and utilizing health care service through time and other factors could be attributed to place, and social context variation between this study and previous studies.…”
Section: Discussionmentioning
confidence: 67%